INTRODUCTION OF PERENNIAL WHEAT TO CONSERVE THE BIODIVERSITY AND SOIL FERTILITY OF THE SOUTHERN AND SOUTHEASTERN REGIONS OF KAZAKHSTAN (Experimental biology, 2021)
Currently, due to the increase in acreage for agriculture, the most important indicator of the environment is the deterioration of soil fertility.  A perennial wheat plant is being grown and adapted in the greenhouses for the first time in Kazakhstan since 2020. The length of the ears of annual wheat averaged 12-12.5 cm, the ears of the variety of perennial wheat-15-16 cm. The longest Ear reached 17 cm in length. In greenhouse conditions, new types of fertilizers with the addition of sulfur were used for the growth and development of perennial wheat. In conclusion, it should be noted that in greenhouse conditions, under the condition of applying fertilizers with the addition of sulfur, compared with the control variant, the growth and development of perennial wheat had higher indicators.  In the conditions of arable land, the composition of soils was determined, an agrobiological experience of growth and development was carried out.